Household contact investigation for the detection of active tuberculosis and latent tuberculosis: A comprehensive evaluation in two high-burden provinces in Iran. (January 2022) - Ghanaiee, R.M.; Karimi, A.; Hoseini-Alfatemi, S.M.; Seddon, J.A.; Nasehi, M.; Tabarsi, P.; Fahimzad, S.A.; Armin, S.; Akbarizadeh, J.; Rahimarbabi, E.; Azimi, L.
Abstract: Background: Systematic evaluation of household contacts of persons with pulmonary tuberculosis (TB) in low- and middle-income countries is recommended by the World Health Organization (WHO). This study recruited adult household contacts of diagnosed TB patients in two high burden provinces of Iran to estimate the prevalence and incidence of active disease and latent TB infection (LTBI) among individuals exposed to TB cases. Methods: We conducted a cohort study among adults in household contact with a pulmonary TB index case. All subjects were assessed for active disease through evaluation of symptoms. Tuberculin skin test (TST) and QuantiFERON®-TB Gold Plus (QFT-Plus) were used to define LTBI. These tests were performed at the time of the index TB case diagnosis and repeated if the previous result was negative, at three-, 12-, and 18-months post recruitment. In addition, interferon-γ-induced protein-10 (IP-10) concentrations were measured in QFT-Plus supernatants for all participants three months after diagnosing the index case. Results: A total of 451 individuals who had close contact with 95 active TB patients were enrolled in this study. Five (1.1%) contacts were diagnosed with active TB and 285 (63.2%) were identified with LTBI during our study. The incidence rate of LTBI among adult household contacts of TB index cases was 0.44 per person per year. Conclusion: The overall rate of LTBI was high. Systematic screening of all household contacts of pulmonary TB should be expanded in Iran to make the timely achievement of the global end TB strategy feasible.